Conceptual design and experimental verification study of a special-shaped composite arch bridge. (February 2021) - Lu, Pengzhen; Zhang, Junping; Li, Dengguo; Zhou, Yutao; Shi, Qingtian
Abstract: This paper presents experimental and analytical modal analyses of the Shizhi River Bridge, which is a concrete-filled steel tubular special-shaped composite arch bridge, with a span of 110 m, and is located in Zhongshan City, Guangdong Province, China. A three-dimensional finite element model (FEM) was developed, and an analytical modal analysis was performed to determine the static behavior, natural frequencies, and mode shapes of the bridge. Static, stabilized, and dynamic field tests were conducted under static loading and forced excitations. The experimental procedures included a static study under five different load conditions. Modal parameter estimations were made based on the acquired data. The first two instability modes were identified in the frequency range of 10–22 Hz using different techniques. The experimental results were compared with those obtained from a three-dimensional finite element model developed in this work. According to the results of the field modal tests, the spectra of the first two hammering models are obtained. Both sets of results were in good agreement with each other. The developed FEM is suitable for long-term monitoring and safety evaluation of bridges under severe environmental conditions such as earthquakes and wind loading.